An experimental investigation of CNT reinforced polymer matrix composites - Muhammad Raihan Zainuldin (2015)
Carbon nanotubes (CNTs) have been known to possess extraordinary mechanical properties that have captured worldwide interest since its discovery. Its hype has brought about tons of research and studies that not only serve to understand its properties and behaviour, but also to find means of reaping its promising benefits. This study aims to validate the findings of other research papers, stating that mechanical properties of CNT based polymer composites can be heightened with the increasing addition of CNTs, but only applicable up to a certain threshold volume fractions (~ 0.15 wt%). However, addition of CNTs above this limit can still produce the reinforcing effect, in fact to a larger extent, if there is excellent distribution, dispersion and alignment of CNTs altogether. Through various experimental methods, namely the tensile test, impact test and hardness test; the tensile properties, toughness and hardness of the relevant materials can be studied. The materials of concern are neat Polycarbonate (PC), and its composites with 1, 2 and 5 wt% Multi-walled Carbon Nanotubes (MWCNT). Twin screw extrusion is utilised to mix the PC and MWCNT. Experimental results showed that at high wt% CNT loadings, reinforcement effect of CNTs diminishes in relative to the neat PC, and the experimental values vary from the theoretical by large. The former points to the fact that the presence of CNTs creates stress internally as they tend to form agglomerates, while the latter can be attributed to some experimental limitations. Agglomeration is due to strong van der Waals forces within CNTs that encourages CNT-CNT interaction. As a consequence, mechanical properties of composites suffer due to the lack of interfacial PC-CNT interaction. However, when comparisons are made only between the composites, enhanced mechanical properties were seen with increasing wt% CNT. It is arguable that the capabilities of CNTs should not be confined to within the stated threshold limits. Rather there exist a strong believe that the effects of CNTs can be multiplied at high wt% and with these achievable means, CNT based composites can be produced at macroscale for commercial intent. This requires the supplement of more sophisticated modern technologies, in conjunction with scientific and engineering findings.